Produktivitas Klon Katuk (Sauropus androgynus (L.) Merr.) Triploid pada Berbagai Kombinasi Perlakuan Pemupukan dan Waktu Pemangkasan - Juhaeti, Titi; Lestari, P.; Utami, N W (JURNAL BIOLOGI INDONESIA, 2015)
Ease of access, affordability and continuity of katuk production is important to support a variety of supplements industry-katuk based being developed at this time. The problem is the existing clones and its cultivation technique has not been able to fulfil the market needs. Therefore clone assembling was done to produce triploid katuk with larger leaves size. In this paper we put forward the research on the fertilization and pruning time that appropriate to support the leaf production of triploid katuk. The study was carried out at the experimental plot in Botany Division of Research Center for Biology-LIPI. The experimental designs was Nested RCBD Design, the main plot were 2 level of pruning time (P1: 3 Weeks After First Pruning (MSPP) and P2: 5 MSPP). The subplots were fertilization (K: Control, B: Beyonic, B ÃÂ¼: Beyonic + NPKÃÂ¼, B ÃÂ½:ÃÂ  Beyonic+ ÃÂ½ dose NPK and NPK: NPK without Beyonic). The growth parameters observed were plant height, number of leaves, the leaf size, were done every week until 8 weeks after planting (WAP). The first pruning to harvest shoots were done at 8 WAP, and the next pruning were done according pruning time treatment i.e. P1 and P2. The pruning was done 3 times. The variables observed at pruning time were shoot length, number of leaves, leaf size, the pruned fresh weight and the fresh weight of edible parts. The result indicated that the triploid katuk clones showed a good response to fertilization both growth and leaf production. The biofertilizers can be combined with the use of inorganic fertilizers to increase edible part of pruning harvest production.ÃÂ Keywords: pruning time, bioorganic fertilizer, triploid katuk, pruning harvest productionÃÂ